Supporting the competitiveness of the Vietnamese economy (Paris, 2011)
Administrative simplification in Viet Nam has reached a defining moment. In 2007, the government launched "Project 30", the goal of which was to reduce administrative procedures by 30% as part of ambitious reforms to modernise the public service and simplify the regulatory environment for businesses. These reforms support the development of infrastructure, increased productivity, greater foreign direct investment and a high rate of growth. Administrative simplification efforts, once fully implemented, will enhance regulatory quality and stimulate competitiveness and equitable growth. It was within this context that Viet Nam invited OECD to evaluate achievements so far and suggest future directions, including options for a ten-year programme for regulatory reform grounded in international best practice. This report details Project 30 and related initiatives. Using international comparisons and incorporating experience from similar reforms in other countries, it explores how Viet Nam can rapidly bring about the full potential of Project 30 and introduce a complete range of regulatory reform instruments in the near future. The lessons learnt from the management of a major administrative simplification initiative in Viet Nam will be useful to other countries seeking to improve their regulatory framework and to reduce administrative burdens, especially in the developing world and in transition countries.
Keywords: Administrative procedure,Thủ tục hành chính; Vietnam,Việt Nam